Turning Restriction Into Change: Imagine-Self Perspective Taking Fosters Advocacy of a Mandatory Proenvironmental Initiative - Uhl-Haedicke, Isabella; Klackl, Johannes; Muehlberger, Christina; Jonas, Eva (Frontiers in Psychology, 2019)
Mandatory policies are needed to mitigate environmental problems but often elicit resistance if individuals perceive them as freedom restrictions. Encouraging people to take the perspective of individuals who suffer from environmental problems may help increase support. This should especially be the case with imagine-self as opposed to imagine-other perspective taking, because the former elicits more personal involvement than the latter. To test this hypothesis, we conducted two studies in which we announced the introduction of a voluntary versus a mandatory proenvironmental initiative and asked people to take an imagine-self versus imagine-other perspective on an individual who suffers from human-caused environmental problems. The imagine-self condition increased the support of mandatory compared to voluntary initiatives. In addition, we found an influence of environmental attitude: The mandatory initiatives received higher support than voluntary initiatives by environmentally minded individuals. These findings highlight imagine-self perspective taking as a potentially useful tool for implementing proenvironmental policies.